Analisis Pengaruh Penggunaan Teknik Inline Terhadap Kebutuhan Air PDAM di Sawojajar dan Kaliwlingi Brebes - Al Bashri, M Hasan; Imron, Imron; Yunus, M (CV. Rayyan Dwi Bharata, 2025)
This study aims to evaluate the effect of using an inline system on the water supply of the Regional Drinking Water Company (PDAM). With the increasing need for clean water in the community, the effectiveness of the water distribution system becomes very important. The research method used is a quantitative approach with experimental and observational designs. The research sample consisted of 200 PDAM customers who were randomly selected from areas that use inline and non-inline systems. Data were collected through questionnaires, direct measurements of water quality, and documentation from PDAM. The results of the analysis show that the use of an inline system has a significant effect on the quantity and quality of water supply. Customers who use the inline system experience increased water pressure and clarity, as well as more stable pH parameters compared to customers who do not use the inline system. These findings indicate that the implementation of an inline system can improve the efficiency of water distribution and meet the community's need for clean water. This study provides recommendations for PDAM to consider expanding the implementation of the inline system in an effort to improve service to customers.